CORPUS-BASED ANALYSIS: “WOMEN” FOR “LEADERSHIP” - Fitri Dianitasari (ETNOLINGUAL, 2021)
Language has often been used as the object of research and examines what is contained in it such as grammatical shifts, vocabulary additions, and also the norms that develop in society. In the study of grammar, there is what is called a corpus which is often used by researchers to help obtain data which will then be processed further. Language contains words, phrases, clauses and sentences. From language studies, it can be used to analyse the tendency of people’s perspective of a leadership, and its relation to woman. Kouzes dan Posner (1991) believe that leadership is an art in mobilizing others to fight for the same thinking. These statements are not biased only for one gender only. However, in reality, not many leaders or leaders who have successfully served are women. The collocation facility owned by the corpus can determine the identity of a word with the accompanying word. by hypothesizing the possibility of an opportunity for women to get collocations with leadership characteristics, instead the results are much different. The word woman is not allocated much with the word leadership characteristics, it is more often associated with sexual issues.